ICT and rural municipalities: are their websites the cores of the local social networks? - Owsiński, Jan W.; Pielak, Aneta M. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
The paper presents the prerequisites for and the initial results from the TIROLS project, financed through a grant from the Polish Ministry of Science and Higher Education, concerning local connections through the intermediary of the websites. The work constitutes a continuation of the earlier research, conducted since 2003, in the domain of evaluation of the local authority websites. The purpose of the work presented is to collect the data on the connections of the municipality websites and the analysis of these connections from the point of view of characteristics of networks thus produced, as well as an attempt of juxtaposing these characteristics with the socio-economic features of the local units. After presentation of the prerequisites for the project, the paper gives the initial results of research, indicating a broad range of features of communes in the domain considered, implying the need for a deeper insight into the role of the municipality websites with this respect.

Artykuł przedstawia założenia i wstępne wyniki badań w ramach projektu TIROLS, finansowanego przez grant MNiSW, dotyczącego powiązań lokalnych za pośrednictwem stron internetowych. Praca stanowi kontynuację badań, prowadzonych od r. 2003, w zakresie oceny stron internetowych samorządów lokalnych. Celem pracy jest zebranie danych na temat powiązań stron internetowych gmin i ich analiza z punktu widzenia cech wewnętrznych tworzonych w ten sposób sieci, a także próba zestawienia charakterystyk tych sieci z cechami społeczno-gospodarczymi badanych gmin. Po przedstawieniu założeń projektu artykuł prezentuje wstępne wyniki badań, wskazujące na znaczą rozpiętość cech stron internetowych gmin w badanej dziedzinie, co stanowi poważny asumpt do głębszego zainteresowania badaną rolą stron internetowych samorządów.